2017
DOI: 10.1093/toxsci/kfx228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systematic Variation in Size and Surface Coating of Silver Nanoparticles on Their In Vitro Toxicity to Macrophage RAW 264.7 Cells

Abstract: In literature, varying and sometimes conflicting effects of physicochemical properties of nanoparticles (NPs) are reported on their uptake and effects in organisms. To address this, small- and medium-sized (20 and 50 nm) silver nanoparticles (AgNPs) with specified different surface coating/charges were synthesized and used to systematically assess effects of NP-properties on their uptake and effects in vitro. Silver nanoparticles were fully characterized for charge and size distribution in both water and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…This is likely because extracellular silver ions, which are internalized to much lower extent than AgNPs, directly interact with sulfydryl groups on membrane proteins and impair membrane permeability, thus causing sudden cell death above a certain concentration , . On the other hand, AgNPs were previously shown to be readily taken up by macrophages, and to gradually release silver ions intracellularly, which allows cells to tolerate nanoparticulate silver at higher concentrations than ionic silver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely because extracellular silver ions, which are internalized to much lower extent than AgNPs, directly interact with sulfydryl groups on membrane proteins and impair membrane permeability, thus causing sudden cell death above a certain concentration , . On the other hand, AgNPs were previously shown to be readily taken up by macrophages, and to gradually release silver ions intracellularly, which allows cells to tolerate nanoparticulate silver at higher concentrations than ionic silver.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, AgNPs were shown to be efficiently taken up by macrophages via scavenging receptors, and to reach maximum intracellular accumulation within less than three hours of exposure . Once inside macrophages, AgNPs have been shown to localize both in endosome‐like structures and the cytoplasm,, where they gradually dissolve into silver ions, thus affecting different organelles such as mitochondria , , …”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the physicochemical descriptors are both size related and combine the size of the pristine NP core (as measured with electron microscopy) with the NP’s behaviour within a specific medium (hydrodynamic diameter). NP core size was linked with cytotoxicity in the past [ 89 , 90 , 91 , 92 , 93 , 94 ] with decreasing size related to higher toxicity. This was usually in conjunction with the assay parameter of exposure dose, since on a constant mass basis there will be much higher numbers of smaller particles relative to larger ones [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Li et al (2016) demonstrated that NPs had higher cytotoxicity and autophagy dysfunction in human bronchial epithelial BEAS-2B cells when compared to an equivalent mass of microscale particles [ 90 ], with both end-points varying in a size- and dose-dependent manner. RAW 264.7 cells [ 91 , 93 ] also demonstrated a size- and dose-dependent relation with cytotoxicity, with smaller particles related to higher toxicity. Makama et al (2018) found that the Ag NP size-dependent toxicity was evident for the production or reactive oxygen species (ROS) [ 91 ], while Loan et al (2018) demonstrated higher toxicity of Au NPs (5 vs. 30 nm nominal sizes) [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RAW 264.7 response is considered to reflect the potential human de novo response, and consequently this cell line is used to evaluate the viability of the product. 33,34 Therefore, in this study, the viability of AgNPs was determined using the RAW 264.7 cell line. RAW 264.7 cells were seeded in 96-well plates in DMEM supplemented with 10% FBS and incubated for 1 h in the presence of various concentrations of EP/AgNPs (140, 280, 420, and 560 µg/mL); the cells were then stimulated for 4 h with 20 ng/mL lipopolysaccharide (LPS).…”
Section: Cell Viability Testmentioning
confidence: 99%